Effect of micronutrient powder supplementation for two and four months on hemoglobin level of children 6–23 months old in a slum in Dhaka: a community based observational study. Issue 1 (December 2016) - Mahfuz, Mustafa; Alam, Mohammed; Islam, M; Mondal, Dinesh; Hossain, M; Ahmed, A; Choudhury, Nuzhat; Raihan, Mohammad; Haque, Rashidul; Ahmed, Tahmeed
Abstract Background Anemia is pervasive among children under the age of two years in Bangladesh. This study aimed to assess the effect of daily supplementation of multiple micronutrient powder (MNP) for 2 months and 4 months primarily on hemoglobin status of children aged 6–23 months living in a slum of Dhaka, Bangladesh. Methods It was a community-based observational study where a total of 402 children and 578 children were enrolled for 2 months and 4 months MNP supplementation respectively. Venous blood was collected at enrollment and 5 months later. Hemoglobin level was measured and morbidity episodes recorded from twice weekly home visits. Results At enrollment, hemoglobin levels were 10.57 ± 1.28 g/dl and 10.78 ± 1.35 g/dl across 2 months and 4 months MNP supplementation groups respectively, compared to 10.65 ± 1.36 g/dl and 11.14 ± 1.11 g/dl at the end-line after MNP supplementation. Plasma hemoglobin increased only after 4 months supplementation in difference-in-difference analysis and this was significantly more in younger children after adjusting the confounding variables (p =  0.03). Prevalence of anemia had improved for both at 2 months (p =  0.015) and 4 months (p =  0.004) of MNP supplementation. Incidence rate ratios (IRR) for diarrhea, cough and fever were comparable across the groups during the supplementation periods and IRR for acute lower respiratory tract infection was significantly lower in 4 months supplementation group with a IRR of 0.30 (95 % CI; 0.22, 0.42). Conclusion Four months MNP supplementation was relatively more effective in improving hemoglobin level in children 6–24 months.